A CRITIQUE OF PHANEROZOIC CLIMATIC MODELS INVOLVING CHANGES IN THE CO2 CONTENT OF THE ATMOSPHERE - Boucot A.J.; Gray J. (My University, 2001)
Critical consideration of varied Phanerozoic climatic models, and comparison of them against Phanerozoic global climatic gradients revealed by a compilation of Cambrian through Miocene climatically sensitive sediments (evaporites, coals, tillites, lateritic soils, bauxites, calcretes, etc.) suggests that the previously postulated climatic models do not satisfactorily account for the geological information. Nor do many climatic conclusions based on botanical data stand up very well when examined critically. Although this account does not deal directly with global biogeographic information, another powerful source of climatic information, we have tried to incorporate such data into our thinking wherever possible, particularly in the earlier Paleozoic. In view of the excellent correlation between CO2 present in Antarctic ice cores, going back some hundreds of thousands of years, and global climatic gradient, one wonders whether or not the commonly postulated Phanerozoic connection between atmospheric CO2 and global climatic gradient is more coincidence than cause and effect.
Keywords: Paleozoic; Miocene; Cambrian; Палеозой; Кайнозой::Неоген::Миоцен; Paleozoic::Cambrian; Cenozoic::Neogene::Miocene; Paleozoic; Палеозой::Кембрийская